En opplyst samtale: Om rettsvitenskapens oppgaver i kriminalpolitikken - Morten Holmboe (Nordisk Tidsskrift for Kriminalvidenskab)
English title: Title in English: An enlightened public discourse: On the tasks of legal research regarding criminal politics